Diagnostic ratio of nitrated phenols as a new method for the identification of pollution emission sources. (1st January 2023) - Yan, Juping; Wang, Xiaoping; Gao, Shaopeng; Gong, Ping; Dotel, Jagdish; Pokhrel, Balram
Abstract: Nitrated phenols (NPs) are emitted from biomass burning and vehicles emissions, or produced by oxidation of phenolic precursors. Previous studies have investigated the emission factors of NPs from various primary emission sources. However, there is no study on the source apportionment method for the diagnostic ratio of NPs. In this study, a new source apportionment method is established using a diagnostic ratio of NPs. Two categories (methyl-nitrocatechols and methyl-nitrophenols) of NP diagnostic ratios, are proposed for source apportionment of primary aerosols. In order to show the accuracy of this source apportionment method, it was applied to the source apportionment of atmospheric NPs in both urban (Kathmandu, Nepal) and remote areas (Lulang, Tibetan Plateau, China). The results show that biomass burning is a common emission source for atmospheric NPs in Kathmandu and Lulang, with vehicle emissions being another important emission source. The atmospheric NPs in the urban area of Kathmandu are commonly from gasoline motorbike emissions, while the atmospheric NPs in Lulang derive from diesel vehicles, throughout the year. The conclusions of the source apportionment study were consistent with the actual vehicle types of local residents in Kathmandu and Lulang, which further proves the reliability of the NP diagnostic ratios method. Graphical abstract: Image 1 Highlights: Nitrated phenols (NPs) ratios were established for aerosol's source identification. This new method was applied to source apportionment of aerosols in different areas. The temporal variation of the atmospheric NPs in different area was clarified.